The Effectiveness of Story Mapping Technique in Teaching Reading Narrative Text - Taufik Kurniawan; Ria Kamilah Agustina (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this study is to analyze the Effectiveness of story-mapping techniques in teaching narrative text reading. The method used in this study is the method experiment; the researcher chose the group pre-test and post-test design. The population of this research was all the students in the eighth grade at SMPN 5 Jombang, consisting of nine classes and a total of 279 students. The researchers examine the data after gathering it. The story mapping method is an effective approach for improving students' reading skills. This Effectiveness is achieved when the score is statistically significant, with a p-value lower than 0.05 in a two-tailed test. The result is known that student learning achievement in learning narrative texts in classes using story mapping techniques has increased significantly compared to classes without story map techniques. This statement is in accordance with data collection calculations by comparing the observation t value (to = 2.35) with the t table (tt = 2.00). It can be seen that to is higher than tt (to >tt). In conclusion, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. Therefore, teaching reading narrative texts using story mapping techniques is effective at SMPN 5 JOMBANG.